Kajian Teknis Geometri Peledakan berdasarkan Analisis Blastability Index untuk Mencapai Target Fragmentasi Ideal dan Diggability PC2000 Komatsu pada Material keras Seam D2, C2 dan DU di PIT 7 West PT. Bukit Makmur Mandiri Utama Jobsite Binungan-Suaran, Kabupaten Berau, Provinsi Kalimantan Timur - Fellya Septia Fauzi; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2021)
Abstract Determining the blasting geometry and blasting material filling must pay attention to the characteristics of the rock’s mass and geological conditions to obtain the ideal fragmentation, where the boulder size is less than 15% with a maximum size 1/3 of the bucket loader used. An alternative geometry experiment had conducted to solve the problem of boulder fragmentation and blasting hard material so the digging equipment rate could increase according to Komatsu's PC2000 plan productivity at PT. BUMA Jobsite BINSUA. An alternative geometry design is determined by researching the rock mass characteristics based on Lili's Blastability Index, includes the Rock Mass Description, Joint Plane Spacing, Joint Plane Orientation, Specific Gravity Influency, and Hardness. Therefore, the actual rock value had obtained from the blasting location and the alternative geometry recommendation using the R.L.Ash theory combined with the Vertical Energy Distribution theory. On C2 layer with 5.95 of the rock factor value recommended burden 7.2 m, space 8.3 m, and a VED explosive charge of 48%. On the D2 layer, the rock factor value is 6.89 with a load of 7.5 m, space 8.3 m, and 55% filling of explosives VED. Besides, on the DU layer, the rock factor value is 6.39 with a load of 7.3 m, space 8.4 m, and 51% filling of the explosive VED. The prediction of blasting fragmentation analysis used Kuz-ram theory obtained fragmentation > 100 cm is 14.99% for the C2 layer, 14.84% for the D2 layer, and 14.82% for the DU layer.Keywords: Blastibility Index, Fragmentasi, Blasting Geometry, R.L.Ash, VED